Communication and Media - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The media, which provides the framework for the information society of the 21st century, influences people’s lives in many ways and through many channels as the fourth branch of power. This is true directly for young people and the professionals who work with them, and indirectly for younger generations through the latter. The image that the mass media paints of certain social groups or generations, the way in which their characteristics are presented, and the extent to which the written press is supportive or critical, all have serious consequences for the people concerned. For example, the continuous negative portrayal of a specific group of professionals, be they teachers or police officers, strongly influences parents’ attitudes towards teachers, schools, or those responsible for public safety, which ultimately serves as a model for children.Therefore, the aim of this chapter is to review the most important information related to mass communication, mass media, and the media in order to strengthen media literacy.Keywords: mass media, mass communication, methods of media, function of mass media, information selection, media literacy